2016
DOI: 10.1186/s13229-015-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on the neuroanatomy of children with autism spectrum disorders: a support vector machine case-control study

Abstract: BackgroundGenetic, hormonal, and environmental factors contribute since infancy to sexual dimorphism in regional brain structures of subjects with typical development. However, the neuroanatomical differences between male and female children with autism spectrum disorders (ASD) are an intriguing and still poorly investigated issue. This study aims to evaluate whether the brain of young children with ASD exhibits sex-related structural differences and if a correlation exists between clinical ASD features and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
78
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 124 publications
9
78
0
4
Order By: Relevance
“…Increasingly, the behavioral characteristics and functionalities of the “male brain” have been cited as risk factors and characteristics of autism spectrum disorders (Baron-Cohen et al, 2005). Imaging studies separately comparing boys and girls with autism to those without autism, are now being conducted, and suggest sex-specific structural network disruptions underpinning the neurobiology of the disorder (Lai et al, 2013, Retico et al, 2016). …”
Section: Sex Differences In Brain Structure Over the Lifespanmentioning
confidence: 99%
“…Increasingly, the behavioral characteristics and functionalities of the “male brain” have been cited as risk factors and characteristics of autism spectrum disorders (Baron-Cohen et al, 2005). Imaging studies separately comparing boys and girls with autism to those without autism, are now being conducted, and suggest sex-specific structural network disruptions underpinning the neurobiology of the disorder (Lai et al, 2013, Retico et al, 2016). …”
Section: Sex Differences In Brain Structure Over the Lifespanmentioning
confidence: 99%
“…However, this possibility has to be raised with great caution; we were not able to also conduct female‐only analyses because of limited sample size, and we cannot therefore rule out the alternative explanation that the greater AUC values in the male‐only analyses simply reflected the use of a gender‐homogeneous sample. Nevertheless, it is interesting to note that one recent ML‐based structural MRI study of prototypical neurodevelopmental autism spectrum disorders showed a similar degree of improvement on discrimination performance in male‐only SVM analyses, but not in analyses restricted to a female subgroup of the same size . Thus better, classification results in male‐only SVM analyses carried out with disorders such as autism or childhood‐onset ADHD may not simply be because of the use of homogeneous groups in regard to gender.…”
Section: Discussionmentioning
confidence: 97%
“…Further, the structural alterations observed in females appeared in different brain regions as compared to males, in particular reduced volume of temporal and frontal cortices, which has been observed in adults (Craig et al 2007;Ecker et al 2017), as well as young children in a reversed pattern (Retico et al 2016). Indeed, little overlap in brain structure alterations associated with ASD might exist between sexes (Lai et al 2013).…”
Section: Quantitative and Qualitative Structural Brain Differencesmentioning
confidence: 92%
“…For example, decreased cortical thickness is observed in females with ASD, as opposed to increased cortical thickness in males with ASD, in the inferior and middle temporal lobes (Ecker et al 2017). Therefore, both quantitative and qualitative neuroanatomical differences in association with autistic traits might be expected between males and females, as previous research indeed indicates (Bloss and Courchesne 2007;Craig et al 2007;Schumann et al 2010;Lai et al 2013;Schaer et al 2015;Retico et al 2016). Using a withinpair design provides valuable insights into neuroanatomical sex differences by testing if autistic trait differences within female twin pairs are associated with more structural brain differences compared to male twin pairs.…”
mentioning
confidence: 99%